Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (SpringerLink, 2024)
Antifreeze proteins (AFPs) are proteins with affinity towards ice and contribute to the survival of psychrophiles in subzero environment. Limited studies have been conducted on how AFPs from psychrophilic yeasts interact with ice. In this study, we describe the functional properties of an antifreeze protein from a psychrophilic Antarctic yeast, Glaciozyma antarctica. A cDNA encoding the antifreeze protein, AFP4, from G. antarctica PI12 was amplified from the mRNA extracted from cells grown at 4 °C. Sequence characterisation of Afp4 showed high similarity to fungal AFPs from Leucosporidium sp. AY30, LeIBP (93 %). The 786-bp cDNA encodes a 261-amino-acid protein with a theoretical pI of 4.4. Attempts to produce the recombinant Afp4 in Escherichia coli resulted in the formation of inclusion bodies (IB). The IB were subsequently denatured and refolded by dilution. Gel filtration confirmed that the refolded recombinant Afp4 is monomeric with molecular mass of ~25 kDa. Thermal hysteresis (TH) and recrystallisation inhibition assays confirmed the function of Afp4 as an antifreeze protein. In the presence of Afp4, ice crystals were modified into hexagonal shapes with TH values of 0.08 °C and smaller ice grains were observed compared with solutions without AFP. Structural analyses via homology modelling showed that Afp4 folds into β-helices with three distinct faces: a, b and c. Superimposition analyses predicted the b-face as the ice-binding surface of Afp4, whereby the mechanism of interaction is driven by hydrophobic interactions and the flatness of surface. This study may contribute towards an understanding of AFPs from psychrophilic yeasts.